Osteoarthritis of the knee joint: an eight year prospective study. Issue 11 (November 1989) - Massardo, L; Watt, I; Cushnaghan, J; Dieppe, P
Abstract : Thirty one patients (25 women, six men, mean age 71.7 years) with established osteoarthritis (OA) of the knee were examined clinically and radiologically on two occasions, eight years apart. Four patients thought they had got better, two of whom had striking functional improvement. Seven remained the same and 20 patients got worse, two needing knee surgery and many developing severe disabilities. Most of the patients had a history of slow acquisition of OA at new joint sites, hand disease emerging as the commonest other site of involvement. Changes in symptoms, disability, and radiographs did not correlate. Three of the four patients who improved symptomatically lost range of motion at the knee and developed more severe changes on their radiographs. Chondrocalcinosis of the knee was seen in five patients, including two of those who improved.